Cavitation-enhanced extravasation for drug delivery. - Arvanitis, C; Bazan-Peregrino, M; Rifai, B; Seymour, L; Coussios, C (2011)
A flow-through tissue-mimicking phantom composed of a biocompatible hydro-gel with embedded tumour cells was used to assess and optimize the role of ultrasound-induced cavitation on the extravasation of a macromolecular compound from a channel mimicking vessel in the gel, namely a non-replicating luciferase-expressing adenovirus (Ad-Luc). Using a 500 KHz therapeutic ultrasound transducer confocally aligned with a focussed passive cavitation detector, different exposure conditions and burst mode timings were selected by performing time and frequency domain analysis of passively recorded acoustic emissions, in the absence and in the presence of ultrasound contrast agents acting as cavitation nuclei. In the presence of Sonovue, maximum ultraharmonic emissions were detected for peak rarefactional pressures of 360 kPa, and maximum broadband emissions occurred at 1250 kPa. The energy of the recorded acoustic emissions was used to optimise the pulse repetition frequency and duty cycle in order to maximize either ultraharmonic or broadband emissions while keeping the acoustic energy delivered to the focus constant. Cell viability measurements indicated that none of the insonation conditions investigated induces cell death in the absence of a therapeutic agent (i.e. virus). Phase contrast images of the tissue-mimicking phantom showed that short range vessel disruption can occur when ultra-harmonic emissions (nf0/2) are maximised whereas formation of a micro-channel perpendicular to the flow can be obtained in the presence of broadband acoustic emissions. Following Ad-Luc delivery, luciferase expression measurements showed that a 60-fold increase in its bioavailability can be achieved when broadband noise emissions are present during insonation, even for modest contrast agent concentrations. The findings of the present study suggest that drug delivery systems based on acoustic cavitation may help enhance the extravasation of anticancer agents, thus increasing their penetration distance to hypoxic regions and poorly vascularised tumour regions.